DEVELOPMENT OF THE QUALITY OF LIFE OF THE ELDERLY IN THE LOCAL ADMINISTRATION OF MUEANG PHITSANULOK DISTRICT PHITSANULOK PROVINCE - Kaewiem, Sakchai; Bodeerat, Chot; Taomit, Sonchai (Journal of MCU Nakhondhat, 2025)
Research objectives 1) To study the level of quality of life development for the elderly in local administrative organizations in Mueang Phitsanulok District, 2) To study the factors affecting the development of quality of life for the elderly in local administrative organizations in Mueang Phitsanulok District, and 3) To propose guidelines for the development of quality of life for the elderly in local administrative organizations in Mueang Phitsanulok District. This study was a mixed-method research. The key informants were 28 people. The interviews were conducted with 1) The Office of Social Development and Human Security of Phitsanulok Province, 2) A political scientist, 3) A local administrative executive, 4) A director of the local administrative organization social welfare division, 5) A director of the sub-district health promoting hospital, 6) A village health volunteer, and 7) A representative of the elderly in local administrative organizations in Mueang Phitsanulok District. The purposive sampling method and a sample of 400 people were selected from a random sample of the elderly in local administrative organizations in Mueang Phitsanulok District. Data were collected by questionnaires. Data analysis used statistics, mean, standard deviation, and multiple regression analysis. The results showed that 1) The level of quality of life development for the elderly in local administrative organizations in Mueang Phitsanulok District The overall picture is at a high level ( = 3.57). 2) Factors affecting the development of the quality of life of the elderly in local administrative organizations, Mueang Phitsanulok District (y) with statistical significance at the .01 level consisted of 4 variables. The order of the effect on the variation from most to least is education (X2 Beta = .506), life security (X1 Beta = .242), economy (X3 Beta = .178), and society (X4 Beta = .089). 3) Guidelines for developing the quality of life of the elderly in local administrative organizations, Mueang Phitsanulok District, found that government organizations should continuously implement guidelines for developing the quality of life of the elderly in local administrative organizations for long-term effectiveness.